Performance of educational personnel in school data management in Madrasa Tsanawiyah - Yulianti, Heni (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aims to find out and obtain in-depth information about the performance of education personnel in managing school data at MTs Negeri 2 Bandar Lampung by looking at: (1) the competence of madrasa administration staff; (2) motivation of madrasa administrative staff and (3) feedback as the service quality of madrasa administrative staff. This research is a qualitative descriptive study. The place that became the object of research was MTs Negeri 2 Bandar Lampung. The subject of this research is the head of madrasa administration staff. The informants in this study were the madrasa administrative staff themselves, the madrasa principal, teachers, students, and the community. Methods of data collection using interviews, observation, and documentation. Test the validity of the data using triangulation of sources and methods. The data analysis technique used is done interactively which includes: data reduction, data presentation, and concluding. The results of the study show that the competencies possessed by each madrasa administrative staff are by their respective fields which include personality competence, social competence, managerial competence, and technical competence. The motivation given by the head of the madrasa and the head of administrative staff to each administrative staff is still not optimal, especially the lack of monitoring and evaluation so that it affects the performance of administrative staff in carrying out their duties. Feedback as the quality of service provided by administrative staff to customers, namely students, all madrasa employees, and the community is quite satisfactory so that many parents entrust MTs Negeri 2 Bandar Lampung as the school of choice, both domiciled near or far from the madrasa.